COMMUNITY-BASED TERRITORIAL DEFENSE: STRENGTHENING CIVIL PARTICIPATION IN SAFEGUARDING NATIONAL SECURITY IN BORDER AREAS - Agung Wahyu Nurkoco; Rudi Sokabla; Jakfar Rosi; Ahmad Faisol; Raul Gomez (Cognitionis Civitatis et Politicae, 2026)
Border areas face increasingly complex security challenges that cannot be effectively addressed through state-centric approaches alone, highlighting the need for inclusive strategies that incorporate local communities. Civil participation plays a critical role in enhancing situational awareness, early threat detection, and collaborative security practices. This study aims to examine the role of community-based territorial defense in strengthening civil participation and improving national security outcomes in border areas. A mixed-methods design was employed, combining quantitative survey data from 200 border residents with qualitative insights from community leaders and security personnel. Data were analyzed using descriptive and inferential statistics alongside thematic analysis to capture both measurable trends and contextual dynamics. Findings indicate that active community participation significantly correlates with improved perceived security, reduced localized threats, and enhanced coordination with security institutions. Institutional trust and access to training emerge as key predictors of participation, while social cohesion strengthens sustained engagement. The study concludes that community-based territorial defense provides an effective and context-sensitive framework for enhancing national security by integrating local knowledge, institutional support, and participatory governance. Sustainable implementation requires structured programs, trust-building mechanisms, and alignment with socio-cultural conditions in border regions.